2015
DOI: 10.1111/cga.12113
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations in sperm associated with male infertility

Abstract: The most common form of male infertility is a low sperm count, known as oligozoospermia. Studies suggest that oligozoospermia is associated with epigenetic alterations. Epigenetic alterations in sperm, which may arise due to the exposure of gametes to environmental factors or those that pre-exist in the sperm of infertile individuals, may contribute to the increased incidence of normally rare imprinting disorders in babies conceived after assisted reproductive technology using the sperm of infertile men. Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 132 publications
(219 reference statements)
1
31
0
Order By: Relevance
“…Several studies have demonstrated that an alteration in the sperm epigenome negatively affects fertility and the future embryo [Castillo et al 2015;Hammoud et al 2010;Kitamura et al 2015]. Therefore, sperm epigenetic evaluation seems necessary before ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that an alteration in the sperm epigenome negatively affects fertility and the future embryo [Castillo et al 2015;Hammoud et al 2010;Kitamura et al 2015]. Therefore, sperm epigenetic evaluation seems necessary before ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in DNA methylation-mediated genomic imprinting have been observed more frequently in men with oligoasthenoteratozoospermia and oligozoospermia (115). However, whether methylation defects in imprinted genes will affect the development and growth processes of ART offspring remains to be elucidated.…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 99%
“…If both the establishment and maintenance of epigenetic machinery are costly, then environmental conditions both during development and during adult life may be expected to affect the epigenome. Such costs may be expected to apply to the maintenance of the epigenome in the soma as well as the germ-line, where epigenetic changes resulting from environmental perturbations can be transmitted to offspring (Lambrot et al 2013;Guerrero-Bosagna and Skinner 2014;Kitamura et al 2015). This could explain why both juvenile and adult environments are sometimes found to influence paternal effects on offspring fitness (Ducatez et al 2012; Adler and Bonduriansky 2013; Braun and Champagne 2014; Fricke et al 2015;Macartney et al 2017).…”
Section: Is Epigenetic Machinery Costly To Build and Maintain?mentioning
confidence: 99%